Design and Analysis of a Photonic Crystal Based Biosensor Working at THz Frequency Region - Ghosh, Bratati; Rahman, Shukufe; Habib, Ahsan; Das, Subrata (Dhaka University Journal of Science, 2015)
2D Photonic Crystal is investigated to find photonic band gap for the purpose of biosensing at THz frequency region. Several structures, one consisting of air holes in Si background and the others consisting of air holes filled with different analytes of having different Refractive Index (RI) in same Si background are considered. For each structure the change in photonic band gap due to the change in RI is observed and shown graphically. By comparing this plot with a standard chart of RI of different materials, any unknown biological analyte can be identified. Thus a biosensing method is developed by using the relationship between RI and band gap of photonic crystals. By comparing and calculating from the relationship; the maximum sensitivity of the developed biosensor is found to be 66.6%. DOI: http://dx.doi.org/10.3329/dujs.v62i1.21952 Dhaka Univ. J. Sci. 62(1): 7-9, 2014 (January)